The effects of electron beam irradiation on the thermal properties, fatigue life and natural weathering of styrene butadiene rubber/recycled acrylonitrile–butadiene rubber blends - N. Z., Noriman; H., Ismail (Elsevier Ltd., 2011)
Link to publisher's homepage at www.elsevier.com/